Factors associated with changes in psychological resilience of older adults with mild cognitive impairment during the COVID-19 pandemic - Matsumoto, Nanae; Kuroda, Yujiro; Sugimoto, Taiki; Fujita, Kosuke; Uchida, Kazuaki; Kishino, Yoshinobu; Arai, Hidenori; Sakurai, Takashi (Frontiers in Aging Neuroscience, 2023)
Introduction: Psychological resilience is an indicator of mental health, but there has been no research to date on changes in psychological resilience among older adults with mild cognitive impairment (MCI) during the stress of the coronavirus disease 2019 (COVID-19) pandemic including factors related to those changes. To fill the gap, this study examined the factors and the changes in psychological resilience of older adults with MCI during the COVID-19 pandemic. Methods: One hundred thirty participants completed the 10-item version of the Connor-Davidson Resilience Scale (CD-RISC-10) between December 2020 and June 2021 as a baseline assessment and between December 2021 and February 2022 as a follow-up. Participants also answered questions on sleep quality, depression symptoms, activities in daily living (ADL), instrumental ADL and social participation to explore factors associated with changes. Results: In this cohort, the mean CD-RISC-10 scores were significantly higher than the baseline at follow-up (p < 0.05), indicating the improvement of psychological resilience. In multiple regression analyses, sleep quality was significantly correlated with change in CD-RISC-10 score (coefficient = 3.94, 95% confidence interval = 1.11 to 6.78). Discussion: Psychological resilience could improve even during the stress of the COVID-19 pandemic in older adults with MCI who were at risk of developing dementia. The factor associated with improved psychological resilience was good sleep quality.